Nutrition : science, issues, and applications - Brehm-Curtis, Barbara (Greenwood, an imprint of ABC-CLIO, LLC, 2015)
"Nutrition is a popular but often misunderstood topic, one about which there is a great deal of interest as evidenced by the plethora of available advice. Because nutrition is a key factor in health, it is important that the public have a source of information they can trust. This is that source: a comprehensive overview that will help readers make sense of conflicting information they find in the media regarding what is healthy and what is not. Organized alphabetically, the two-volume work covers the most important topics in human nutrition including nutrients, nutrition-related health concerns"--Publisher's website.